Journal of Human Sport and Exercise - 2021 - Winter Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc3.34
|View full text |Cite
|
Sign up to set email alerts
|

Development of digital literacy and competence of future sports teachers in the physical and educational environment

Abstract: Thanks to the rapidly evolving technology, today's students are improving along with the digital world. The aim of this research was to study the level of students' knowledge of digital technology (computer, tablet computer, laptop, smartphones, interactive whiteboard and other digital devices). The authors used the following approachesobservation, comparative investigations and synthesis of modern techniques to the formation of digital competencies of students, analysis of science, sociological, pedagogical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Characteristics of Educational Needs in the Era of Society 21 st century or the era of society 5.0 is the rapid development technology in the world such as the Internet of Things (internet for everything), Artificial Intelligence, Big Data (large amounts of data), and robots. It creates a new paradigm for the education field, where education must be able to create professional individuals who are able to control the progress of the future, have competitiveness, and be competent to adjust to the massive technological developments (Salimzyanova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of Educational Needs in the Era of Society 21 st century or the era of society 5.0 is the rapid development technology in the world such as the Internet of Things (internet for everything), Artificial Intelligence, Big Data (large amounts of data), and robots. It creates a new paradigm for the education field, where education must be able to create professional individuals who are able to control the progress of the future, have competitiveness, and be competent to adjust to the massive technological developments (Salimzyanova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the most productive and focused part aimed at improving digital knowledge and students' ability to demonstrate their level of digital skills (Salimzyanova et al, 2021).…”
Section: Human Developmentmentioning
confidence: 99%
“…The European Union is focused on ensuring that basic education and teacher training are in place to support the continuous flow of digital skills among students (Education & Training, 2020). To promote digital skills and digital competence, students must understand the importance of using digital technologies and computers (Salimzyanova et al, 2021). Digital capabilities provide a critical role in the sustainability of community development (Yuen et al, 2018).…”
Section: Human Developmentmentioning
confidence: 99%
See 2 more Smart Citations